2004
DOI: 10.1093/jn/134.10.2673
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-6 Is Greater in Preadipocytes than in Adipocytes of 3T3-L1 Cells and C57BL/6J and ob/ob Mice

Abstract: Inflammation plays a major role in the development of chronic diseases such as cardiovascular disease and Type 2 diabetes. Further, it was demonstrated that obese animals and humans have significantly higher levels of circulating proinflammatory cytokines, such as interleukin-6 (IL-6). The aim of this study was to determine whether adipose tissue could be a major source of circulating IL-6 in leptin-deficient obese (ob/ob) mice by comparing the expression of IL-6 in different tissues of ob/ob mice. Our seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
102
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(118 citation statements)
references
References 27 publications
13
102
2
1
Order By: Relevance
“…As previously reported [1], we confirmed the increased expression of Tnf in the WAT from mice with diet-induced obesity, while no alteration of Il6 expression was found. This is in contrast to the previously reported overexpression of Il6 in the WAT of genetically obese ob/ob mice [28], which, however, have a much more pronounced increase in fat mass than our model of diet-induced obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…As previously reported [1], we confirmed the increased expression of Tnf in the WAT from mice with diet-induced obesity, while no alteration of Il6 expression was found. This is in contrast to the previously reported overexpression of Il6 in the WAT of genetically obese ob/ob mice [28], which, however, have a much more pronounced increase in fat mass than our model of diet-induced obesity.…”
Section: Discussioncontrasting
confidence: 99%
“…Others already suggested differences in the capacity of adipokine production by pre-adipocytes compared to mature adipocytes. [52][53][54] We demonstrated that adiponectin was mainly produced by adipocytes, while IL-6 and PAI were produced by both adipocytes and pre-adipocytes, but pre-adipocytes produced more IL-6 and PAI than adipocytes.…”
Section: Discussionmentioning
confidence: 79%
“…Based on immunoselective isolation of cell fractions, they suggest that the major contributors of CXCL5 in adipose tissue are macrophages present in the stromal vascular fraction. However, the use of IL-6 and MCP-1 as specific markers for macrophages in the selection process is misleading because these proteins are also highly expressed in preadipocytes (29,41). Therefore, the relative contribution of macrophages and preadipocytes to both CXCL5 and KC expression by the stromal vascular fraction deserves further study.…”
Section: Discussionmentioning
confidence: 99%